Strategies to Produce Cost-Effective Third-Generation Biofuel From Microalgae - Rafa, Nazifa; Ahmed, Shams Forruque; Badruddin, Irfan Anjum; Mofijur, M.; Kamangar, Sarfaraz (Frontiers in Energy Research, 2021)
Third-generation biofuel produced from microalgae represents a promising alternative to address the growing concerns of global energy insecurity and climate instability. Even though the current global algal biomass production stands at 38 million liters, its commercialization faces several bottlenecks in terms of economic feasibility. However, cost minimization strategies, particularly for microalgae cultivation, have largely been excluded from recent studies. Therefore, this review provides essential insights into the technologies and economics of cost minimization strategies for large-scale applications. Cultivation of microalgae with aquafarming, in wastewater, or with biogas upgrading, and co-production of value-added products (VAPs) with biodiesel can significantly lower the production cost of microalgae-based biodiesel. Despite several technical issues that remain to be evaluated properly, economic analysis has revealed that incorporating these cost-effect strategies can make the biorefinery concept feasible and profitable. The cost for producing microalgal biodiesel can be lowered to up to 0.73kg-1 dry weight when cultivated in wastewater or 0.54L-1 when co-produced with VAPs. Most importantly, access to co-product markets with higher VAPs needs to be encouraged as the global market for microalgae-based VAPs is estimated to rise to 53.43 billion in 2026. Therefore, policies that incentivize research and development, and the production and consumption of microalgae-based biodiesel are important to reduce the large production cost gap that often persists between biodiesel and petroleum diesel.